Water Inrush Characteristics with Roadway Excavation Approaching to Fault - Shuren Wang; Hu Wang Hu Wang (Universitas Ahmad Dahlan, 2012)
Water inrush disaster is an important factor in restricting safe production of the coal mine. Taking the roadway in seam in Danhou Coal Mine, as the engineering background, according to the spatial relationship of the roadway, the impermeable layer, the fault and the loading conditions, the fault activation mechanical model under the roadway excavation disturbance was built, and the fault activation conditions, roadway water inrush criterion and water inrush three modes were put forward. A three-dimensional numerical calculation models were built by using FLAC3D. Through fluid-solid coupling calculation, the surrounding rock damage and failure, the water inrush channel formation, and the evolution process of water inrush of the roadway excavation approaching the fault were analyzed. Moreover, the displacement field, the stress field and the surrounding rock plastic failure characteristics of the roadway were revealed. Furthermore, under the conditions of different water pressure, impermeable rock thickness, fault displacement, and fault dip angles, the roadway water inrush modes and their evolution characteristics were comparatively analyzed.